Strategi Pengembangan Bisnis Pada Masa Pandemi Covid-19 Studi Kasus Pada PT. BPRS Artha Madani - Mega Juliani Putri; Fajri Ryan Isnandar (LPPM Universitas Islam 45, 2022)
The challenge in Islamic banking during the Covid-19 pandemic was liquidity and the ratio of non-performing financing (NPF). In addition, the uneven liquidity in the banking industry has caused some banks to enjoy excess liquidity and others to lack funds. Due to the pandemic condition, PT BPRS Artha Madani lost liquidity from third party funds within 3 months as many as 98 depositors made large withdrawals. The purpose of this research is to provide alternative suggestions for new strategies in the business development of PT. BPRS Artha Madani during the covid-19 pandemic.The data analysis technique in this study used SWOT analysis through interviews with the management of PT BPRS Artha Madani who has the authority to make decisions for the company and has an understanding of the research topic. Then analyzed through the Quantitative Strategic Planning Matrix or QSPM to determine which strategy will be prioritized in the selection of the recommended alternative strategies through the SWOT matrix.The results show that the highest score (Total Attractiveness Score) or TAS of 19.166 is Creating a personal e-commerce platform belonging to BPRS Artha Madani, an alternative name, namely Artha Madani Market. Because during this pandemic, people prefer to do online transactions at home to minimize the spread of covid-19.